2015
DOI: 10.1371/journal.pone.0109414
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Agreement of Corneal Power Measurements Obtained Using a New Corneal Topographer OphthaTOP

Abstract: PurposeTo evaluate repeatability and reproducibility of anterior corneal power measurements obtained with a new corneal topographer OphthaTOP (Hummel AG, Germany) and agreement with measurements by a rotating Scheimpflug camera (Pentacam HR, Oculus, Germany) and an automated keratometer (IOLMaster, Carl Zeiss Meditec, Germany).MethodsThe right eyes of 79 healthy subjects were prospectively measured three times with all three devices. Another examiner performed three additional scans with the OphthaTOP in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
(42 reference statements)
0
11
1
1
Order By: Relevance
“…The CoV of all K values were less than 0.3%, and the Sw and 2.77Sw of all parameters were no more than 0.17 D and 0.25 D, respectively, and the ICCs were no more than 0.97. In Huang et al’s study[ 35 ], the intraobserver repeatability and interobserver and intersession reproducibility of all measured parameters showed a CoV of less than 0.24%, a 2.77Sw of 0.29 D or less, and an ICC of more than 0.906. Wang et al[ 29 ] evaluated corneal power measurements from eight devices and found good intraobserver repeatability and interobserver and intersession reproducibility with Medmont E300 (with 32 Placido rings and measuring 9,600 points for every scan), EyeSys Vista (with 26 Placido rings and measuring 9,360 points for every scan) and Allegro Topolyzer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The CoV of all K values were less than 0.3%, and the Sw and 2.77Sw of all parameters were no more than 0.17 D and 0.25 D, respectively, and the ICCs were no more than 0.97. In Huang et al’s study[ 35 ], the intraobserver repeatability and interobserver and intersession reproducibility of all measured parameters showed a CoV of less than 0.24%, a 2.77Sw of 0.29 D or less, and an ICC of more than 0.906. Wang et al[ 29 ] evaluated corneal power measurements from eight devices and found good intraobserver repeatability and interobserver and intersession reproducibility with Medmont E300 (with 32 Placido rings and measuring 9,600 points for every scan), EyeSys Vista (with 26 Placido rings and measuring 9,360 points for every scan) and Allegro Topolyzer.…”
Section: Discussionmentioning
confidence: 98%
“…However, for the data that is near zero, the CoV is too sensitive to have usefulness. In the present study, because both J0 and J45 were close to zero, we didn’t calculate the CoV for them[ 29 , 35 ]. The ICCs evaluated the consistency for data sets of repeated measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Sirius was shown to have better agreement compared to Pentacam in keratometry compared to Orbscan . Good agreement in anterior keratometry was observed between Pentacam and another Placido disk device, OphthaTOP …”
Section: Comparison Among Different Devices: Repeatability and Agreementmentioning
confidence: 78%
“…[53][54][55][56] Good agreement in anterior keratometry was observed between Pentacam and another Placido disk device, OphthaTOP. 57 A good agreement was noted between Scheimpflug and OCT devices in unoperated eyes, but most studies only confirmed the high correlations of measurements among devices without affirming their interchangeability. In other studies, significant differences were shown in mean keratometry between Pentacam and different OCT devices.…”
Section: Agreementmentioning
confidence: 92%
“…Recientes estudios aparecidos en la literatura científica demuestran que este tipo de errores pueden ser minorizados por los nuevos topógrafos corneales, no influyendo de forma significativa en la adquisición y tratamiento de datos (Hong et al, 2013;Huang et al 2015), por lo que la comunidad médica oftalmológica acepta la existencia de estos errores, los cuales considera despreciables en comparación con la valiosa información que aportan los topógrafos para el diagnóstico de las patologías ectásicas corneales.…”
Section: Errores Intrínsecosunclassified